Empirical Study on the Factors Influencing Muslim Consumers' Decision-Making in Choosing Halal Products in Indonesia - Rizka Ar Rahmah; Erni Yusnita Siregar; Nurintan Siregar (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the factors influencing Muslim consumers' decisions in choosing halal products in Indonesia. With increasing awareness of the importance of halal products, this study examines the influence of religious awareness, halal label perception, social and cultural influences, product quality, price, and the role of social media on halal product purchasing decisions. Data were collected through questionnaires distributed to 200 respondents, as well as in-depth interviews with consumers. Data analysis was conducted using multiple linear regression to examine the relationship between independent variables and purchasing decisions, and a moderation test to examine the role of social influence as a moderating variable in the relationship between religious awareness and purchasing decisions. The results showed that religious awareness, halal label perception, social and cultural influences, and product quality significantly influenced purchasing decisions for halal products, with a significance threshold of p < 0.05. In contrast, price did not have a significant impact on purchasing decisions (p = 0.120). The role of social media was found to have a positive influence on purchasing decisions for halal products (p = 0.055), although its influence was smaller compared to other factors. These findings have important implications for companies, policymakers, and the public in increasing understanding and access to quality halal products.